Adapting Research to a Global Pandemic: A Fully Remote Actigraphy and Ecological Momentary Assessment Study. Issue 2 (March 2022) - Vigoureux, Taylor F. D.; Mu, Christina X.; Mason, Tina M.; Gonzalez, Brian D.; Lee, Soomi
Abstract : Background: Mandated social distancing practices and quarantines in response to COVID-19 have resulted in challenges for research on healthcare workers, such as hospital nurses. It remains unknown whether nursing studies utilizing complex methodology like sleep actigraphy and ecological momentary assessment (EMA) can be conducted remotely without compromising data quality. Objectives: We aimed to (a) disseminate our remote study protocol for sleep actigraphy and EMA data from hospital nurses during COVID-19, (b) assess feasibility and acceptability of this approach for studies on hospital nurses, and (c) examine the reliability and ecological validity of sleep characteristics measured across 14 days. Methods: Using an online platform, we provided 86 outpatient nurses from a cancer hospital with detailed video/text instructions regarding the study and facilitated virtual study onboarding meetings. Feasibility was assessed by comparing adherence rates to a similar in-person study of nurses from the same hospital; acceptability was evaluated through content analysis of qualitative study feedback. Multilevel modeling was conducted to assess changes in sleep characteristics as a function of study day and daily stressful experiences. Results: Adherence to EMA (91.8%) and actigraphy (97.9%) was high. EMA adherence was higher than the in-person study of inpatient day-shift nurses from the same hospital. Content analyses revealed primarily positive feedback, with 51.2% reporting "easy, clear, simple onboarding" and 16.3% reporting the website was "helpful." Six participants provided only negative feedback. Sleep characteristics did not change as a function of study day except for self-reported quality, which increased slightly during Week 1 and regressed toward baseline after that. A higher incidence of stressor days or higher stressor severity followed nights with shorter-than-usual time in bed or poorer-than-usual sleep quality, supporting the ecological validity for these methods of assessing sleep in nurses. Discussion: Findings suggest that a fully remote study protocol for EMA and actigraphy studies in nursing yields robust feasibility, acceptability, reliability, and validity. Given the busy schedules of nurses, the convenience of this approach may be preferable to traditional in-person data collection. Lessons learned from COVID-19 may apply to improving nursing research postpandemic.